Molecular Insight into Mycobacterium tuberculosis Resistance to Nitrofuranyl Amides Gained through Metagenomics-like Analysis of Spontaneous Mutants - Igor Mokrousov; Ivaylo Slavchev; Natalia Solovieva; Marine Dogonadze; Anna Vyazovaya; Violeta Valcheva; Aleksey Masharsky; Olesya Belopolskaya; Simeon Dimitrov; Viacheslav Zhuravlev; Isabel Portugal; João Perdigão; et al. (MDPI AG, 2022)
We performed synthesis of new nitrofuranyl amides and investigated their anti-TB activity and primary genetic response of mycobacteria through whole-genome sequencing (WGS) of spontaneous resistant mutants. The in vitro activity was assessed on reference strain Mycobacterium tuberculosis H37Rv. The most active compound 11 was used for in vitro selection of spontaneous resistant mutants. The same mutations in six genes were detected in bacterial cultures grown under increased concentrations of 11 (2×, 4×, 8× MIC). The mutant positions were presented as mixed wild type and mutant alleles while increasing the concentration of the compound led to the semi-proportional and significant increase in mutant alleles. The identified genes belong to different categories and pathways. Some of them were previously reported as mediating drug resistance or drug tolerance, and counteracting oxidative and nitrosative stress, in particular: Rv0224c, fbiC, iniA, and Rv1592c. Gene-set interaction analysis revealed a certain weak interaction for gene pairs Rv1592-Rv1639c and Rv1592-Rv0224c. To conclude, this study experimentally demonstrated a multifaceted primary genetic response of M. tuberculosis to the action of nitrofurans. All three 11-treated subcultures independently presented the same six SNPs, which suggests their non-random occurrence and likely causative relationship between compound action and possible resistance mechanism.